From Extensive Reading to Critical Writing: Using Drama Plays to Develop University Students’ Critical Gender Literacy - Huzaimah Mudrika; Nadrah Nadrah; Andriadi Andriadi (Jurnal Kajian Ilmu Pendidikan (JKIP), 2026)
Critical gender literacy has become an essential competency for university students, enabling them to critically examine gender representation, stereotypes, and power relations presented in literary texts. However, many EFL students still experience difficulties in moving beyond literal comprehension to critically interpret gender issues and express informed perspectives in their writing. Extensive reading using drama plays offers meaningful opportunities for students to engage with authentic social issues while fostering critical reflection and literacy development. This study aimed to investigate how extensive reading through drama plays contributes to the development of university students’ critical gender literacy. A mixed-methods design was employed involving 75 undergraduate students from the English Language Teaching Study Program. Data were collected through classroom observations, semi-structured interviews, students’ reflective journals, and writing assessments. The findings revealed that sustained engagement with drama plays enabled students to identify gender stereotypes, analyze power relations, question traditional gender norms, and develop a deeper understanding of gender equality. Students also became more reflective readers by connecting literary texts with real-life social contexts and expressing their critical perspectives through evidence-based responses. These experiences demonstrate that extensive reading can effectively support students in transforming critical reading into critical writing while strengthening their awareness of gender issues. In conclusion, extensive reading using drama plays is an effective pedagogical approach to developing university students’ critical gender literacy by promoting critical reading, reflective thinking, and informed responses to gender issues in literary and social contexts.